Analisis Pengaruh Parameter Mesin Bubut Konvensional Terhadap Kesilindrisan Permukaan Baja ST 42 Menggunakan Metode Box Behnken Design - Nadia Musharofah; Pranowo Sidi; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The dimensional accuracy of the workpiece might be impacted by geometric variations that machines frequently experience. The geometric shape of the workpiece as a result of the machining process can be used to quantify machine quality and can take the form of cylindricality, smoothness, roundness, and other geometric shapes. The results of the workpiece surface's cylindricality will depend on machining parameters such engine rotation, feed speed, and feed depth. For the design of the research experiment and the data analysis, this study employs the Box Behnken Design in Response Surface Method that is figuring out the trial variation using 3 stages. The specimen used was ST 42 steel, and a DNMG 150404 carbide insert tool was used on a Pinacho L-1/260 conventional lathe to perform a total of 15 experimental modifications on the specimen. Furthermore, the cylindricity test was carried out using a dial indicator. The research results on the effect of parameters on surface cylindricity, namely engine speed with a Pvalue of 0.068, depth of feed with a Pvalue of 0.784, and feed speed with aPvalue of 0.839, the three parameters were declared not to have a significant effect. The engine rotation parameter provides a contribution effect of 26.87%, the depth of feed is 0.52% and the feed speed is 0.28%.